Eco-Green Catalys: An Intelligent Distribution Network for Generative Mycorrhizal Spores Through AI and Iot Optimization for Ecological Complexity Engineering in Post-Deforestation Lands Based on Restorative Bio-Economy Principles - Mahmudi, Gilang Arya; Lestari, Dwi Puji; Arianto, Davina Anindya Cindy (IDRIS Darulfunun Institute, 2026)
The ecological crisis caused by illegal deforestation has resulted in severe soil degradation, biodiversity loss, and disruption of ecosystem balance. Eco-Green Catalys emerges as an adaptive biotechnological innovation integrating Artificial Intelligence (AI) and the Internet of Things (IoT) to accelerate the restoration of post-deforestation lands. This system operates through an intelligent distribution network of generative mycorrhizal spores, which precisely controls inoculation, moisture regulation, and nutrient delivery based on real-time soil data analysis. Supported by a Spatio-Temporal Deep Learning (STDL-AI) framework, the system demonstrates up to 96% accuracy in ecological monitoring, enhances vegetation recovery rates by 70%, and increases carbon sequestration capacity by 35% compared to conventional restoration methods. Beyond ecological rehabilitation, this innovation reinforces the principles of restorative bio-economy by utilizing renewable energy sources and community-based participation, aligning with the Sustainable Development Goals (SDG 13) on climate action and long-term ecological resilience. Overall, Eco-Green Catalys provides a scalable and data-driven model that bridges environmental technology and socio-economic sustainability in restoring tropical ecosystems.